2011
DOI: 10.1038/onc.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

HMGA proteins promote ATM expression and enhance cancer cell resistance to genotoxic agents

Abstract: DNA-damaging therapies represent a keystone in cancer treatment. Unfortunately, many tumors often relapse because of a group of cancer cells, which are resistant to conventional therapies. High-mobility group A (HMGA) proteins has a key role in cell transformation, and their overexpression is a common feature of human malignant neoplasias, representing a poor prognostic index often correlated to anti-cancer drug resistance. Our previous results demonstrated that HMGA1 is a substrate of ataxiatelangiectasia mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 38 publications
(51 reference statements)
7
57
0
Order By: Relevance
“…We employed small interfering RNA (siRNA)-mediated HMGA2 KD and confirmed a general protective function exerted by endogenous HMGA2 against fork cleavage, as indicated by a significant increase in the amount of fragmented DNA seen in the comet tails when endogenous HMGA2 levels were reduced by about 50% ( Figure 3D). Together, these results are in excellent agreement with previous findings that revealed significant protective effects of HMGA2 against drug-induced DNA damage in mouse embryonic fibroblasts and in human cancer cells expressing exogenous HMGA2 (Palmieri et al, 2011;Summer et al, 2009).…”
Section: Hmga2 Protects Against Nucleolytic Fork Collapsesupporting
confidence: 92%
See 1 more Smart Citation
“…We employed small interfering RNA (siRNA)-mediated HMGA2 KD and confirmed a general protective function exerted by endogenous HMGA2 against fork cleavage, as indicated by a significant increase in the amount of fragmented DNA seen in the comet tails when endogenous HMGA2 levels were reduced by about 50% ( Figure 3D). Together, these results are in excellent agreement with previous findings that revealed significant protective effects of HMGA2 against drug-induced DNA damage in mouse embryonic fibroblasts and in human cancer cells expressing exogenous HMGA2 (Palmieri et al, 2011;Summer et al, 2009).…”
Section: Hmga2 Protects Against Nucleolytic Fork Collapsesupporting
confidence: 92%
“…In addition, the lack of HMGA genes does not alter cell growth, indicating that HMGA proteins are not essential factors for DNA replication (Beitzel and Bushman, 2003;Palmieri et al, 2011). However, when forks are arrested, the presence of HMGA2 protects forks from nucleolytic collapse.…”
Section: Discussionmentioning
confidence: 99%
“…However, other recent research suggested that ATM is also involved in many other cancer signaling pathways other than DNA damage response, which relates to chemoresistance, radioresistance, metastasis, cell growth and proliferation. Chemoresistance may be caused by DNA damage-independent ATM signaling via overexpression of HMGA proteins [42]. Oxidized ATM signaling, supports breast tumor metastasis through the regulation of IL-8 [36].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HMGA1 can significantly upregulate a number of genes involved in cell cycle regulation, signal transduction, neoplastic transformation, and tumor progression in various systems, including CLK-1, cdc25A, cdc25B, cyclin C, JNK2, and p38 MAPK [38]. HMGA1 inhibits the function of p53 family members in thyroid cancer cells, increases the expression of oncogenic miR-222 in lung cancer cells, enhances cancer cell resistance to genotoxic agents, enhances epithelial-mesenchymal transition, and promotes tumor progression in breast cancer cells [25,[38][39][40]. Recent study has shown HMGA1 upregulation to be associated with survival in pancreatic ductal adenocarcinoma whereas downregulation of HMGA1 has enhanced gemcitabine chemosensitivity for suppressing growth of tumor cells [26,41,42].…”
Section: Discussionmentioning
confidence: 99%